(untitled) (Quinto Sol, 2022)
This article analyzes the link between the regional historiography that emerged from the Argentine historiographic renovation of the 1980s and the Malvinas archipelago as a possible object of that history. It is mainly concerned with the renovating historiography that dealt with the colonial period and the early post-revolutionary years. Consistent with existing and emerging agendas, it shows how the Malvinas can (and should) form part of an agenda that takes up the legacy of regional history in the perspective of connected and transnational histories.